Effectiveness of Wood Vinegar from Tobacco Stalk on Termite Resistance in Bamboo (Dendrocalamus asper Backer) - Okta Prima Indahsari (Andalasian International Journal of Entomology, 2024)
Bamboo (Dendrocalamus asper Backer) is commonly used as structural material in the tobacco curing barns of PT Perkebunan Nusantara X, where it is installed in the ground as supporting pillars. However, subterranean termites (Coptotermes curvignathus Holmgren) pose a significant threat to bamboo, causing brittleness and structural damage. This study aimed to identify the most effective wood vinegar treatment to protect bamboo against termite attacks. This research conducted at February 2022 to July 2023 in Jember, East Java, Indonesia. This study used explanatory research methods. Tobacco stalk-derived wood vinegar was applied to bamboo using seven different treatments (labeled A to G), each replicated three times, and compared with untreated control bamboo. Wood vinegar made from tobacco stems is effective in suppressing subterranean termite attacks on bamboo. After 18 months of observation, treatment E—where bamboo was soaked in wood vinegar for one day, followed by the application of one liter of wood vinegar to the surrounding soil—proved to be the most effective. This treatment reduced termite damage by 29% compared to the control and minimized brittleness to only 12%, outperforming the other treatments. Consequently, treatment E is recommended for bamboo used in curing barns to enhance resistance against subterranean termite attacks.